El Maestro journal 1926-1931: A first approach - González Sánchez, David E. (2021)
This paper addresses a first look at the educational journal El Maestro published in Costa Rica between 1926 and 1931. For this purpose, an analysis of the content of the journal was applied to determine a profile of the object of study. The article contextualizes the historical, social, and intellectual environment in which the publication is identified. It also describes the type of content it offers and tries to identify some veins for future research that shed new light on the history of Costa Rican education and pedagogical thought.